BMI of the firstborn offspring at age 12 reflects maternal LDL and HDL cholesterol levels at term pregnancy and postpartum. (June 2014) - Romejko-Wolniewicz, Ewa; Lewandowski, Zbigniew; Zareba-Szczudlik, Julia; Czajkowski, Krzysztof
Abstract Objective: The aim of this study was to assess the relationship between the body mass index (BMI) of the firstborn offspring at age 12 and maternal lipid levels at term and at 6 months postpartum. Design and Methods: The study included children born in the 2nd Department of Obstetrics and Gynecology of the Medical University of Warsaw between 1 November 1991 and 31 May 1993. The end point was BMI in the upper quartile – considered high BMI of the firstborn offspring at age 12. Results: The risk of high BMI in the offspring at age 12 significantly increased with an increase in the LDL-C level at term (OR = 2.41 per SD increase, 95% CI: 1.01–5.80; p < 0.049), a decrease in the HDL-C% at term (OR = 0.35 per SD increase, 95% CI: 0.14–0.84; p < 0.019) and a decrease in the HDL-C level at 6 months postpartum (OR = 0.25 per SD increase, 95% CI: 0.08–0.82; p < 0.022), regardless of maternal weight status before pregnancy and at 6 months postpartum, gestational weight gain, the offspring's gender and birth weight. Conclusion: LDL and HDL cholesterol levels at term are markers of maternal adaptation to a first pregnancy and predict the future growth of firstborn offspring.